2017
DOI: 10.1111/pedi.12513
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous mutation of the WFS1 gene leading to constitutive endoplasmic reticulum stress is the cause of Wolfram syndrome

Abstract: A novel heterozygous mutation of WFS1 induced constitutive ER stress through ATF6α activation and ER Ca efflux, resulting in cell apoptosis. These results provide new insights into the roles of WFS1 in UPR and mechanism of monogenic DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
1
23
2
Order By: Relevance
“…Morikawa et al have found a de novo heterozygous 4 aa inframe deletion (p.N325_I328del) in an 11-month-old Japanese female WS patient with insulin-dependent DM, congenital cataract, and severe bilateral hearing loss (55). Although cataract is not typical of WS1, other cases associated with WFS1 heterozygous mutations have been described (56).…”
Section: Molecular Biology Physiology and Pathophysiology Of Ws1mentioning
confidence: 99%
“…Morikawa et al have found a de novo heterozygous 4 aa inframe deletion (p.N325_I328del) in an 11-month-old Japanese female WS patient with insulin-dependent DM, congenital cataract, and severe bilateral hearing loss (55). Although cataract is not typical of WS1, other cases associated with WFS1 heterozygous mutations have been described (56).…”
Section: Molecular Biology Physiology and Pathophysiology Of Ws1mentioning
confidence: 99%
“…Since SERCA2b is expressed in MAMs and is a well-known effector of ER Ca 2+ uptake 150 , Wfs1 may be a novel MAM physiological effector essential for Ca 2+ homeostasis. In contrast, Morikawa et al 151 described a reduced mRNA level of SERCA2b in HEK-293 cells transfected with mutant WFS1 cDNA compared to HEK-293 cells transfected with wild-type WFS1 cDNA. This elevation of [Ca 2+ ] cyto is associated with an increase of the mRNA level of CCAAT-enhancer-binding protein homologous protein, leading to ER stress-induced cell apoptosis 152 .…”
Section: Is Mams' Dysfunction Playing a Role In Ws1 Pathology?mentioning
confidence: 84%
“…Silencing of Wfs1 by specific shRNA in neurons also induced increased expression of these factors but only to a moderate extent. ER stress caused by Wfs1 deficiency was implicated also in the disruption of β-cell function (Morikawa et al, 2017; Ohta et al, 2017). Wfs1 was also suggested to participate in calcium handling: silencing of Wfs1 by specific shRNA in neurons resulted in depression of calcium transients and of Ca 2+ release from the ER (Cagalinec et al, 2016).…”
Section: Introductionmentioning
confidence: 99%